Uptake of Arsenic by Irrigated Vegetables and Cooked Food Products in Burkina Faso - Clair-Caliot, Guillaume; Marks, Sara J.; Hug, Stephan J.; Bretzler, Anja; N'guessan, N'goran Djo; Tihe, Sussue Franck Kevin; Lalanne, Franck (Frontiers in Water, 2021)
As compared to the Asian lowlands, environmental exposure to arsenic (As) in West Africa has received little attention. Recent studies have found geogenic As contamination of groundwater in many regions in Burkina Faso. As-contaminated groundwater is used for drinking and increasingly also for the irrigation of staple foods. This study assesses the extent to which irrigation and cooking of staple foods in Burkina Faso influence plant uptake and dietary consumption of As, respectively. Using a greenhouse experimental setup, we evaluated the transfer of As from irrigation water spiked with 0, 100, 500, and 1,000 μg/L As(V) to the organs and edible parts of seven commonly consumed vegetables (amaranth, carrot, green bean, lettuce, okra, spinach, and tomato). Next, we cooked the greenhouse-cultivated vegetables and externally purchased foods with As-free and As-spiked waters. The As content in all plant organs increased with increasing As in the irrigation water. With 500 μg/L, the concentrations of As in the edible parts (ordered from highest to lowest) were as follows: spinach (6.6 ± 0.5 μg/g); lettuce (3.9 ± 0.1 μg/g); carrot (3.5 ± <0.1 μg/g); amaranth (2.2 ± <0.1 μg/g); okra (0.9 ± <0.1 μg/g); green bean (0.8 ± <0.1 μg/g); and tomato (0.2 ± <0.1 μg/g). The edible parts of leafy vegetables irrigated with As-spiked water had a higher average As content (4.9 ± 4.5 μg/g) than root (2.9 ± 2.0 μg/g) and fruit/pod vegetables (0.8 ± 1.1 μg/g). Cooking with an excess volume of As-free water reduced the As content in the cooked vegetables by 39% on average, while cooking with As-contaminated water transferred As to the cooked food. The As content in steamed foods was 8 to 18 times lower than in boiled foods. Based on human health risk estimates, we generally recommend to avoid planting leafy and root vegetables in areas with As concentrations above 100 μg/L in irrigation water. In areas with elevated As contamination, mitigation strategies include the cultivation of fruit/pods vegetables such as tomato and okra and steaming the food instead of boiling.